Mortality differentials by educational attainment globally - Moradhvaj Dhakad; Samir KC (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2024)
The mortality status across the population is determined by its level of socioeconomic development. Education significantly impacts a population's health and lifespan, with more educated individuals tending to live longer than their less-educated counterparts. However, the impact of education on mortality may differ across countries, and the evidence on mortality by educational attainment is primarily limited to low-mortality countries. Understanding mortality differentials by educational attainment is critical for social and health policy formation, and for comprehending the current and future prospects of the population. The Wittgenstein Centre (WIC) population projections in 2013 (WIC2013) and 2018 (WIC2018) assumed standardised mortality differentials by educational attainment based on evidence from a limited number of countries. The updated WIC global population projections in 2023 (WIC2023) now account for age-sex-specific heterogeneity in mortality and migration by educational attainment. This paper describes the data and methods used to estimate mortality by educational attainment in the base year globally. Finally, we analyse mortality patterns by educational attainment for males and females across countries using multiple data sources.
Keywords: 300